‘Boy smell’: transgender and nonbinary people’s experiences of bodily smell - Easterbrook-Smith G (Taylor and Francis Group, 2024)
Although smell is sometimes treated with little regard, it is invested with cultural meaning and conveys a great deal of information, including about gender, sexuality and identity. This article draws on interviews with 11 transgender and nonbinary people who have accessed gender affirming hormone therapy (GAHT), and focuses on how they understand and explain changes in how their own bodies smell. Although it is well documented that GAHT causes changes in skin oiliness, changes in smell are inconsistently documented, and within the medical literature are often commented on only in passing. Taking a discourse analytic approach, the article finds that participants noticed changes in their own smell during hormonal transition, that in many cases this change was understood as significant in some way, and that these changes could be experienced as affirming. Understandings of what changes in bodily smell meant were often derived relationally or socially, although participants’ discussion of the experience frequently focused on their own embodiment. Smell seems to form part of a process of (re)identification with the physical self and gender affirmation that can be facilitated by GAHT.
Keywords: transgender health; sensory studies; body odour; gender identity; gender affirming hormone therapy